Acephalgic Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
A 7-year-old girl presenting with a one year history of intermittent migraine auras without headache, a maternal grandfather similarly affected, and a mother with common migraine are reported from McGill University and the Montreal Children's Hospital, Canada.